2011
DOI: 10.1261/rna.030106.111
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional modification of spliceosomal RNAs is normal in SMN-deficient cells

Abstract: The survival of motor neuron (SMN) protein plays an important role in the biogenesis of spliceosomal snRNPs and is one factor required for the integrity of nuclear Cajal bodies (CBs). CBs are enriched in small CB-specific (sca) RNAs, which guide the formation of pseudouridylated and 29-O-methylated residues in the snRNAs. Because SMN-deficient cells lack typical CBs, we asked whether the modification of internal residues of major and minor snRNAs is defective in these cells. We mapped modified nucleotides in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…3). The 5′ portion contains an impressive number of post-transcriptional modifications including 14 pseudouridylations and 10 methylated nucleotides [47][49]. In contrast, no modifications are identified downstream of position 90 of RNU2, and this domain contains more extensive secondary structure, particularly when the precursor sequence is included.…”
Section: Resultsmentioning
confidence: 99%
“…3). The 5′ portion contains an impressive number of post-transcriptional modifications including 14 pseudouridylations and 10 methylated nucleotides [47][49]. In contrast, no modifications are identified downstream of position 90 of RNU2, and this domain contains more extensive secondary structure, particularly when the precursor sequence is included.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, U6 snRNA, whose known guide RNAs concentrate in nucleoli (Tycowski et al 1998;Ganot et al 1999;Darzacq et al 2002), could not be modified when targeted to CBs . The postulate that snRNA modification requires targeting to CBs became untenable when it was shown that snRNA modification still takes place in mutant cells that lack CBs Nizami et al 2010b;Deryusheva et al 2012). Furthermore, snRNAs can be efficiently modified in vitro in cell-free systems (Jády and Kiss 2001;Ma et al 2005;Deryusheva and Gall 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This complex is implicated in the nucleocytoplasmic transport of small nuclear RNAs (snRNAs) and in their maturation to small nuclear ribonucleoproteins (snRNPs) as part of the spliceosomal complex (Akten et al, 2011;Deryusheva et al, 2012;Fischer et al, 1997;Leung et al, 2011;Liu et al, 1997;Makarov et al, 2012;Massenet et al, 2002;Matera and Shpargel, 2006;Sebbag-Sznajder et al, 2012). Studies using different models of SMA have suggested that the severity of the disease could correlate with the inefficiency of snRNP maturation, and as a consequence, to defective splicing of target pre-mRNAs (Chari et al, 2009;Gabanella et al, 2007;Imlach et al, 2012;Lotti et al, 2012;Pellizzoni, 2007;Winkler et al, 2005;Workman et al, 2009;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%